Techno-Economic Analysis of Waste Heat Recovery in Automotive Manufacturing Plants - Putu Diah Prajna Paramita; Sindu Daniarta; Attila R. Imre; Piotr Kolasiński (Applied Sciences, 2025)
This study proposes an innovative system for recovering waste heat from exhaust air after a regenerative thermal oxidiser process, integrating a Carnot battery and photovoltaic (PV) modules. The Carnot battery incorporates an organic Rankine cycle (ORC) with a recuperator, thermal energy storage (TES), and heat pump. Waste heat is initially captured in TES, with additional energy extracted by a heat pump to increase the temperature of a secondary fluid, effectively charging TES from both direct and indirect sources. The stored heat enables electricity generation via ORC. The result of this study shows a heat pump COP between 2.55 and 2.87, the efficiency of ORC ranging from 0.125 to 0.155, and the power-to-power of the Carnot battery between 0.36 and 0.40. Moreover, PV generates 1.35 GWh annually, primarily powering the heat pump and ORC system pump. The proposed system shows a total annual net generation of 4.30 GWh. Economic evaluation across four configurations demonstrates favourable outcomes, with a return on investment between 25% and 160%. The economic evaluation examined configurations with and without the PV system and recuperation process in the ORC. Results indicate that incorporating the PV system and recuperator significantly increases power output, offering a highly viable and sustainable energy solution.